SYSTEM ANALYSIS OF THE SHARING OF SURPLUS PROFITS (SHU) OF THE SOLUSI BERSAMA LAMLHOM SHARIA COOPERATIVE FROM THE PERSPECTIVE OF SYIRKAH AGREEMENT - Nuril Purnama; Azka Amalia Jihad (Prodi Hukum Ekonomi Syariah, Fakultas Syariah dan Hukum, UIN Ar-Raniry, 2025)
This study focuses on analysing the profit-sharing system of the Lamlhom Joint Solution Sharia Cooperative, Lhoknga District, Aceh Besar, from the perspective of the syirkah contract. This is a qualitative study with a legal-empirical approach. The primary data were obtained from structured interviews and observations. Meanwhile, the secondary data was obtained from SHU accountability reports and articles related to this study. The results showed that the SHU distribution system at Kopsyah SBL was implemented by distributing it to all active members as annual packages, without distinction between capital, business services, or the amount of financing taken. All members benefited collectively from the cooperative’s business results. According to the syirkah contract, SHU is not part of the syirkah contract formulation, because SHU is not a profit that is determined at the beginning of the contract between Kopsyah SBL and members who use syirkah contract services. However, the SHU distribution system at Kopsyah SBL is part of the tabarru' (social) contract, which is in line with sharia principles such as fairness, transparency, and mutual agreement, and the SHU distribution system at Kopsyah SBL is legally compliant with sharia principles.